Metagenomic Sequencing of P30-gene-positive Using MinION Sequencer for Apicomplexan Species Identification - Dela Ria Nesti; Ahmad Baidlowi; Lucky Ronald Runtuwene; Ari Indrawati; Wayan Tunas Artama; Yutaka Suzuki (Proceeding of International Conference on Science, Health, And Technology, 2021)
Oxford Nanopore Technologies MinION sequencer is a recent technology of portable, real-time, single molecule long-read DNA/RNA sequencing which has the potential to analyze clinical and environmental samples in the field. Here, we describe the result of metagenomic sequencing from samples with P30-gene-positive using MinION sequencer. One hundred cattle blood samples which were confirmed positive of blood parasites using blood smear method were collected from Diseases Investigation Centre (DIC), Yogyakarta province. After DNA extraction, each sample was amplified by conventional PCR using primers targeting the P30 gene. PCR products were visualized under UV illumination after electrophoresis on 1.5% TBE/agarose gels and stained with SYBR Safe™ DNA gel stain. Twenty-five samples showed the desired 400-bp DNA fragment, which was inferred as P30 gene positive. Four whole cattle blood samples with the highest DNA concentration were sequenced separately using MinION sequence for 24 hours. Sequencing data was then analyzed using bioinformatics tools. Three samples resulted in low sequencing yield and could not be analyzed, but we were able to identify Theileria orientalis as the major pathogen from one sample. We were also able to construct 95.8% of its genome. To our knowledge, this is the first publication of a parasite genome reconstruction from metagenomic sample using MinION sequencer in Indonesia.